2019
DOI: 10.1097/spc.0000000000000404
|View full text |Cite
|
Sign up to set email alerts
|

Māori: living and dying with cardiovascular disease in Aotearoa New Zealand

Abstract: Purpose of reviewThis article provides an informed perspective on cardiovascular disease (CVD) and palliative care need among Ma ¯ori New Zealanders. High Ma ¯ori CVD risk factors will contribute to a sharp increase in older Ma ¯ori deaths which has implications for health and palliative care service provision. Recent findingsCVD is New Zealand's leading cause of premature deaths and disability among Ma ¯ori. A projected rise in older Ma ¯ori deaths within the next 30 years will require increased palliative ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Similar to the global ageing trend, older New Zealanders experience complex conditions affecting their cardiovascular health. 8,9 While the causes of cardiovascular problems are mostly multifactorial and usually have a cumulative genetic and environmental predisposition, 18 there is limited understanding of how these health issues impact older adults in consideration of their health history and common risk factors such as physical inactivity. Our findings provided evidence on specific demographic characteristics of older adults and their HRQOL in relation to cardiovascular health problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to the global ageing trend, older New Zealanders experience complex conditions affecting their cardiovascular health. 8,9 While the causes of cardiovascular problems are mostly multifactorial and usually have a cumulative genetic and environmental predisposition, 18 there is limited understanding of how these health issues impact older adults in consideration of their health history and common risk factors such as physical inactivity. Our findings provided evidence on specific demographic characteristics of older adults and their HRQOL in relation to cardiovascular health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) among New Zealanders continues to rise and is the leading cause of death in New Zealand. 4,8 With longer life expectancies, CVD is increasingly common among older adults and adds to the burden on the health system. 4 It has been reported that older New Zealanders who have cardiovascular health issues have an increased likelihood of hospital readmissions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frailty is also driven by poverty (5,(30)(31)(32). Māori and Pasifika are more likely to have been born into poverty than non-Māori and non-Pasifika (33).…”
Section: Association With Mortalitymentioning
confidence: 99%
“…Low health literacy makes navigating an unfamiliar and complex health system a significant barrier for Māori (30). While equity in health care for Māori and Pasifika is embedded in policy in New Zealand, there is a struggle to put it into practice because cultural and diversity training is not a condition of employment (31).…”
Section: Association With Mortalitymentioning
confidence: 99%